O conhecimento pedagógico do conteúdo (PCK) no ensino do direito: um estudo exploratório. - Vilalva, Adriana Mallmann (2017)
Considering that teachers¿ professional knowledge has strong influence in students¿ learning processes and also that Law School professors have not necessarily been trained in Pedagogical and teaching skills, thus resort to a more dogmatic and teacher-centered style, this study proposes a discussion about the aspects related to Pedagogical Content Knowledge which has been studied in several areas of teacher training, but not deeply enough by the Law professionals in Brazil. In order to better understand the topic, we studied Lee Shulman¿s constructs ¿ Pedagogical Content Knowledge (PCK) and the Pedagogical Reasoning and Action Framework (PRAF). Therefore, the question that triggered this investigation is: to carry out a theoretical research and study of the concept of PCK and what are its repercussions on the teaching practice of a Law school professor; to observe and understand how a teacher assimilated the concept of PCK and how she deals with the content of the subject she teaches and how her teaching practice was shaped. To that end, we used multiple tools for the collection of data: the creation of a field journal that reports the observation of classes of a Law School professor during one school term; interviews; the analysis of her teaching plan, and post-observation questions. Data has been analyzed having the practical proposals formulated by Minayo (2006) and the categories of PRAF, proposed by Shulman. PCK comprises of an important kind of knowledge when establishing bodies of professional knowledge and enables the structuring of teaching practices of Law School professors. Data analysis allowed us to understand that it is not enough knowledge of the specific content of the subject to be taught, you need a body of knowledge to that teaching can be transformed into learning.